Vokabellernen (ohne) Vergessen (mit) Vokabellernstrategien - Cudzich, Bartosz (Glottodidactica, 2012)
The aim of this article is to describe the issue of effective vocabulary learning among the students of neophilological faculties as well as to provide an answer to the question on how to learn vocabulary effectively. To achieve this aim, two vocabulary learning strategies (the key-word method and learning by heart) were compared on the basis of empirical research. Moreover, the vocabulary learning style of the informants was described, the conclusions were drawn and recommendations given.